Coyaima de la Real Corona. Between Legality and violence: Agrarian conflict in an Indian Town during the second half of the 18th century. - Salinas Leal, Héctor Hernando (Pontificia Universidad Javeriana, 2014)
Considering the general tendencies of the Resguardo in colonial Hispanic America, the Indian town of Coyaima de la Real Corona, located in what is today the southern region of the deparment of Tolima, is studied as an unusual Resguardo, not only due to its fundation characteristics but also due to the town's historic process.Founded as "A Town of the Royal Crown" by virtue of the collaboration of the Coyaima in the war against the Pijaos, this settlement, made up of communinty with similar ethnic and cultural characterisicts, was able to conserve a certain degree of political autonomy before the Crown and, in particular, before the local authorities and neighboring hacendados. Freed from forced tribute payments, under a somewhat autonomous goverment, with a homogenous social makeup and extensive communal held lands, Coyaima could forcefully confront the encroachment of the large land holders ovre their territories, especially during the 18th century.